Implementación de BPM´S para mejorar la calidad higiénica en la producción primaria de queso fresco en una microempresa de la ASOPROLAMM. - Rivera Fernández, Renato Agustín (2012)
The Salesian University in July 2010 conducted an investigation into "DIAGNOSIS OF SMALL AND MEDIUM INDUSTRIES DAIRY OF CANTON CAYAMBE". The conclusions of the diagnosis is expressed to be to improve the processes of cleaning and hygiene in the early stages of casting, pressing and packaging of the product also states that there is the presence of E. coli in the hands of the manipulator and that this is a problem that is evident in most companies. Likewise, the recommendations emphasized the need to dictate talks and training to personal hygiene issues. Considering these aspects was the need to intervene in one of the companies for the implementation of good manufacturing practices in primary production in order to improve the quality and safety of products sold in our country.